Microaggressions in the health setting - Martinho, S.; Moleiro, C.; Vauclair, C.-M. (XIV PhD Meeting in Social and Organizational Psychology, 2018)
The aim of this research is to explore, describe and test how minority social healthcare professionals react and handle microaggressions from patients and colleagues; what major themes emerge and which are the implications of this subtle form of discrimination; how implicit bias interfere with individual’s intersecting identities producing differential outcomes; and what are the main consequences for the health care system in general (individual, bystanders, health care climate, and patient outcomes).